Critical Evaluation of a Randomized Clinical Trial (Part II): From the Follow-up of Participants to the Analysis of Results - Sousa-Pinto, Bernardo; Azevedo, Luís (Journal of the Portuguese Society of Anesthesiology, 2018)
.